Development Of The Implementation Of The Principle Of Contradiction Delimitation In The Process Of Complete Systematic Land Registration (PTSL) - Patarida Sitorus, Dian; Gusti Ayu Ketut Rachmi Handayani, I; Karjoko, Lego (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Land registration since the enactment of the basic agrarian law has never produced significant results until the last few years. The Ministry of Agrarian Affairs and Spatial Planning / National Land Agency often looks for ways to speed up land registration with the registration program proposed since 2016, namely the complete systematic land registration (PTSL). One of the important stages in the systematic registration of land is the application of the principle of delimitation contradiction. This study discusses the implementation of the principle of contradiction delimitation that has changed since the systematic land registry was implemented. This study aims to show how the effect of changes in the mechanism of implementation of the STs, especially in the implementation of the principle of contradiction delimitation. The research methods used in this work are normative legal research methods with a focus on positive legal norms as the main material. The results of this research is a change of the mechanism of implementation of the new PTSL resulted in changes in the implementation of the principle of contradiction delimitation. With the new PTSL implementation scheme, land registration is expected to be implemented with a relatively shorter period of time so that it will be more efficient. However, this change reduces the legal certainty of the regulation regarding the application of the principle of delimitation contradiction. The government in making policies is expected to always prioritize the importance of the legal basis for new policies before they are made.